(untitled) (Lex localis - Journal of Local Self-Government, 2025)
It is an inevitable choice in the development of local colleges and universities to speed up the effective construction of disciplines and professional degrees.It is also a major task given to local colleges and universities by the development of higher education in China.However, the gap between local universities and universities affiliated to ministries and commissions determines that local universities can not compete with key universities in the construction and development.Therefore, we should take the discipline specialty as a breakthrough, take the characteristic discipline and the advantage specialty as the lead, and give full play to the advantages of local colleges and universities.Exploring the development of discipline construction and professional degree setting in local universities has become a new path to be solved urgently in the current development of universities.Through the analysis of the value and significance of discipline construction and professional degree setting in local colleges and universities,Taking four local universities in Sichuan Province as the research object, this paper analyzes the current situation of discipline construction and professional degree setting in local universities.Under this condition, this paper finds out the hindrance of the current discipline construction and professional degree setting in local colleges and universities to the cultivation of talents.Finally, targeted improvement strategies are proposed.